A ratiometric theranostic probe for tumor targeting therapy and self-therapeutic monitoring. (October 2016) - Li, Shi-Ying; Cheng, Hong; Xie, Bo-Ru; Qiu, Wen-Xiu; Song, Li-Lin; Zhuo, Ren-Xi; Zhang, Xian-Zheng
Abstract: Feedback imaging-guided precise photodynamic therapy (PDT) can facilitate the development of personalized medicine. In this work, a Förster resonance energy transfer (FRET) based theranostic probe was fabricated for simultaneous tumor targeting PDT and ratiometric imaging of the therapeutic effect. The theranostic probe (designated as P-PpIX) was comprised of a targeting moiety, a caspase-3 responsive linker, a FRET fluorophore pair and a photosensitizer. It was found that P-PpIX exhibited low intrinsic background fluorescence due to the high FRET quenching efficiency. The Arg-Gly-Asp (RGD) targeting moiety allowed P-PpIX to selectively accumulate in αv β3 integrin overexpressed tumor cells. Upon photo irradiation, the PDT effect of P-PpIX could induce cell death with apoptosis related mechanism, and the activated caspase-3 would subsequently cleave the Asp-Glu-Val-Asp (DEVD) peptide sequence to terminate the intramolecular FRET process. The activated caspase-3 expression and the real time therapeutic efficacy could be precisely assessed in situ by the fluorescence intensity ratio of the released 5(6)-carboxylfluorescein (FAM, reporter fluorescence) and protoporphyrin IX (PpIX, internal reference fluorescence). This novel ratiometric theranostic probe could provide the real-time feedback for precise PDT.